Klasyfikacja innowacyjności przestrzeni europejskiej - Strahl, Danuta; Markowska, Małgorzata (Classification of the European Space Innovation, 2005)
The contemporary world development is, to a great extend, determined by the processes of innovation. The enlarged European Union assumes that obtaining high level of innovation, facilitating an effective competition at the global market, becomes the strategic objective for the coming years. Therefore, the study presents an assessment of innovation level diversification in the European Union countries by means of 11 indicators. Classification of the European Union countries has been conducted in order to distinguish groups similar with regard to human resources for innovation, creating new knowledge and financing innovation processes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 605-612